Study of pipe connector effect in piping system - Muhamad Fikri Aziz, Mat Lah (2010)
This thesis was carried out to investigate the effect of connecting pipes in a piping system using acoustic emission techniques. A plumbing system that is equipped with a number of connecting pipes was tested with acoustic emission sensors on the different fluid pressure. The sources of the acoustic emission signals (AE) is the activity prior to and after the fluid through connecting pipes and it is observed using acoustic sensors with a view of software USB E3.34.For study effects of pipe connections, all time domain parameters (maximum amplitude, power, RMS amplitude) of signals were observed and processed with the aid of Matlab software. All parameters were compared with the pressure of the fluid flow at eleven different points. The results showed that the difference between the AE parameters of high-flow pressure and low flow pressure is not much different. From this relationship, it may not conclude that the pipe connecting is the main factor to the difference in acoustic emission technique effects.